Fragile X syndrome carrier screening in pregnant women in Chinese Han population - Hung, Chia-Cheng (Sci Rep, 2019)
Fragile X syndrome (FXS) is the most frequent genetic cause of intellectual disability (ID). It was previously believed that the FXS prevalence was low in Chinese population, and the cost-efficiency of FXS carrier screening was questioned. This retrospective observational study was conducted between September 2014 and May 2017 to determine the prevalence of FXS carriers in a large Chinese cohort of pregnant women. The FMR1 CGG repeat status was determined in 20,188 pregnant Taiwanese women and we identified 26 women with premutation (PM). The PM allele was transmitted to the fetus in 17 pregnancies (56.6%), and six of 17 expanded to full mutation (FM). One asymptomatic woman had a FM allele with 280 CGG repeats. Prenatal genetic diagnosis of her first fetus revealed a male carrying a FMR1 gene deletion of 5′ UTR and exon 1. Her second fetus was a female carrying a FM allele as well. This is so far the largest study of the FXS carrier screening in Chinese women. The prevalence of premutation allele for FXS in normal asymptomatic Taiwanese women was found to be as high as 0.13% (1 in 777) in this study. The empirical evidence suggests that reproductive FXS carrier screening in Taiwan might be cost-effective.